Síntese de membranas compósitas modificadas com óxido de grafeno e polietilenoglicol para remoção de contaminantes emergentes da água - Cadore, Jéssica Stefanello (2023)
The membrane separation process stands out as an efficient technology for removing pollutants from aqueous media. This technology may present some limitations, including pore size, limited selectivity, hydrophobicity, fouling, and low mechanical and chemical resistance. At the national level, another limiting factor is the low production of membranes in Brazil, resulting from the dependence on imported technologies and the need for investments in infrastructure and technical training. Therefore, studies and incentives should be encouraged to obtain improvements in water and effluent treatment techniques. The incorporation of new materials can minimize such limitations and develop advanced processes, such as composite membranes. Among the most recent and promising materials investigated for incorporation into membranes, graphene oxide stands out. Its incorporation into the polymer matrix of membranes confers unique properties, such as greater durability, resistance, and anti-fouling capacity. The addition of graphene oxide can increase filtration capacity and reduce pore size, allowing low molecular weight compounds to be retained. In addition, adding more than one material can provide different characteristics to these membranes. Polyethylene glycol is a low molecular weight polymer and can provide benefits to the structure of membranes, such as increased porosity, permeate flux and hydrophilicity. The general objective of this study was to develop polymeric composite membranes containing graphene oxide and polyethylene glycol for the separation process of the drugs caffeine, diclofenac sodium and amoxicillin dispersed in water. The membranes were synthesized, characterized and evaluated for their efficiency in removing contaminants. The work showed that the addition of graphene oxide improved the structure of the manufactured membranes, reducing the pore size, increasing selectivity and permeability. The addition of polyethylene glycol increased porosity, pore size and permeate flux. On the other hand, it reduced the tensile strength and rejection of the contaminants caffeine, diclofenac sodium and amoxicillin. The addition of the materials changed the morphology of the membranes through larger cavities and wider channels. An increase in roughness was also observed through the incorporation of graphene oxide and a reduction with the addition of polyethylene glycol. The permeability of the membranes increased from 0.6156 L/h.m².bar to 4.5373 L/h.m².bar after the addition of graphene oxide and polyethylene glycol. The hydraulic flux of the synthesized membranes reached 37.81 L/h.m².bar. It can be concluded that the structure and porosity, as well as the rejection of contaminating drugs, were directly influenced by the incorporation of graphene oxide and polyethylene glycol into the membranes. Rejection of up to 80.6% of caffeine, 66% of diclofenac sodium and 87.33% of amoxicillin was observed for the polymeric membrane with the addition of 1.5% graphene oxide loading. This can be considered promising for the removal of emerging contaminants from water.